Case Report: Complete Remission of C1q Nephropathy Treated With a Single Low-Dose Rituximab, a Reality or Coincidence? - Ma, Rui; Wu, Dengyan; He, Zhiqin; Chang, Qian; Yang, Yonghong (Frontiers in Pediatrics, 2021)
C1q nephropathy is a glomerulopathy that is characterized by large amount of C1q deposits in the glomerular mesangium. It is a diagnosis of exclusion after ruling out systemic lupus erythematosus and membranoproliferative glomerulonephritis by systemic and serological examination. The pathogenesis of C1q nephropathy is unclear. In addition, there is very little generalizability in the treatment and prognosis for pediatric C1q nephropathy due to diversities in clinical manifestations and pathological types. Rituximab is a human/mouse chimeric monoclonal antibody against CD20, which is primarily used for treating lymphomas and, most recently, has been used to treat certain kidney diseases including C1q nephropathy. In this report, we used one quarter of the typical dose of rituximab for lymphoma treatment to achieve complete remission in a C1q nephropathy patient, significantly reducing deposition of immune complexes and glomerular damage. This case indicates that dosage reconsiderations may be necessary for rituximab in treatment of pediatric C1q nephropathy.